5.2.2 If \( k(x)=-f(x) \), write down the equation of \( k \). 5.2.3 If \( f(x)=3^{x-1}+2 \) is translated to \( t \) such that \( t(x)= \) (a) Determine \( t^{-1} \) in the form of \( y=\ldots \) (b) Describe the transformation from \( f \) to \( t \).
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To find \( k(x) \), substitute \( f(x) \) into the equation \( k(x) = -f(x) \). Thus, \( k(x) = -\left(3^{x-1}+2\right) = -3^{x-1} - 2 \). For the transformation \( t(x) \), if \( f(x) = 3^{x-1}+2 \) is translated up by a vertical shift of \( m \) units (let’s say \( t(x) = 3^{x-1}+2+m \)), then to find the inverse, set \( y = t(x) \) yielding \( y = 3^{x-1} + 2 + m \). Rearranging gives \( 3^{x-1} = y - 2 - m \), and by taking logarithms and solving for \( x \), we eventually find \( t^{-1}(y) = \log_3(y - 2 - m) + 1 \). The transformation from \( f \) to \( t \) involves a vertical shift, moving the entire graph of \( f(x) \) either up or down depending on the value of \( m \). This means all output values increase (if \( m > 0 \)) or decrease (if \( m < 0 \)) uniformly, altering the graph's height without changing its general shape.